The Effect of Ginger Booking and the Aroma of Lemon Inhalation Therapy Towards Gerdadian Emesis Gravidarum for Pregnant Mothers in Trimester I - Eva Lesrina Asrin Siregar; Zuraidah Nasution; Sarma Lumbanraja (Institute of Computer Science (IOCS), 2022)
Pregnancy is the growth and development of the intrauterine fetus starting from conception and ending until the onset of labor. Nausea and vomiting (emesis gravidarum) is a problem that is often experienced by pregnant women in early pregnancy. To determine the effect of giving ginger decoction and lemon inhalation therapy to the incidence of emesis gravidarum in first trimester pregnant women in the working area of the Marancar Health Center, Kaupaten Tapanuli Seatan in 2021. Methods: The research design used a quasi-experimental approach with a two group pre and post test design approach. The population and sample in the study were 30 people. The data were processed by univariate and bivariate analysis using paired sample t-test and independent t-test. Results : There is an effect of giving ginger stew on reducing the incidence ofadianemesis gravidarumandthere isthe effect of giving lemon inhalation aromatherapy to decreaseadianemesis gravidarum. Giving ginger decoction is more effective than giving lemon inhalation in dealing with the decrease in the incidence of nausea and vomiting in first trimester pregnant women in the Marancar Health Center Work Area in 2021. It is hoped that the results of this study can improve services in the health sector, especially in providing information about the effect of giving boiled ginger and aromatherapy lemon inhalation against canceradianemesis gravidarumin first trimester pregnant women.